Los políticos y su auditorio (II). La interacción asociada con determinados tipos de información: compartida, noticiosa y reproducida - Cortés Rodríguez, Luis (Círculo de Lingüística Aplicada a la Comunicación, 2025)
As part of our study of the politician’s connection with the audience, we will deal here with three different types of information used by the speaker: I. Shared information, which we find in speeches in which the it aims to involve the audience in shared knowledge, although sometimes it is only a pretext for reinforcing one’s own opinion and attacking the rival (“knowing”, “knowing”, “remembering”, etc.); II. News information, which is formulated through expressions in which the politician wishes to make known, in many cases to advance, certain information (“announce”, “say”, “explain”, etc.), and III. Reproduced information, found in expressions in which the speaker appropriates a quote from someone else or from himself, issued with greater or lesser fidelity and which usually serves as support for a part or the rest of the utterance (“say”, “ask”, “according to+verb tense”, etc.). For the analysis, we will start from a corpus consisting of fourteen speeches by Spanish Prime Ministers and opposition leaders during the debates on the state of the nation; this corpus has a duration of 13h58m40s.